Turoctocog alfa pegol provides effective management for major and minor surgical procedures in patients across all age groups with severe haemophilia A: Full data set from the pathfinder 3 and 5 phase III trials. Issue 3 (15th April 2020) - Tosetto, Alberto; Neff, Anne; Lentz, Steven R.; Santagostino, Elena; Nemes, Laszlo; Sathar, Jameela; Meijer, Karina; Chowdary, Pratima; Shen, Chunduo; Landorph, Andrea; Hampton, Kingsley
Abstract: Introduction: Turoctocog alfa pegol is a glycoPEGylated recombinant factor VIII (FVIII) with an extended half‐life developed for prophylaxis, treatment of bleeds and perioperative management in patients with haemophilia A. Aim: Evaluate the efficacy and safety of turoctocog alfa pegol treatment for major and minor surgeries in the pathfinder 3 and 5 phase III trials. Methods: Adults/adolescents aged ≥12 years with severe haemophilia A (FVIII <1%) received perioperative turoctocog alfa pegol treatment planned to achieve FVIII activity levels >80% during major surgery (pathfinder 3). The primary end point was haemostatic efficacy during surgery; secondary end points were blood loss, haemostatic effect postsurgery, consumption, transfusions, safety and health economics. Children (0‐11 years) undergoing minor surgeries received 20‐75 IU/kg turoctocog alfa pegol at Investigator's discretion (pathfinder 5). Results: pathfinder 3 included 35 patients undergoing 49 major surgeries. Haemostasis was successful in 47/49 (95.9%) surgeries; two had moderate haemostatic responses. Median (mean) blood loss during major surgery was 75 (322.6) mL. Four bleeds were reported postsurgery; three were successfully treated with turoctocog alfa pegol (one was not evaluated). On the day of surgery, overall mean (median) dose was 75.5 (74.5) IU/kg and mean (median) number of doses was 1.7 (2.0). Five procedures required 11 transfusions on the day of surgery or days 1‐6. No safety concerns or inhibitors were identified. Forty‐five minor surgeries in 23 children were performed without complications. Conclusion: Turoctocog alfa pegol was effective for perioperative haemostatic management of major and minor surgeries in patients across age groups with severe haemophilia A.